Audit of Information Technology Governance on School Operational Cost Flow in SMKN West Jakarta Using COBIT 2019 - Narul Sakron; Gerry Firmansyah; Habibullah Akbar; Budi Tjahjono (CV. Publikasi Indonesia, 2023)
IT governance is a process that aims to carry out the process of aligning business objectives in an agency in accordance with the business strategy applied to that agency. One sector that is trying to improve IT in improving its governance is the education sector including all SMKNs in West Jakarta. The problem with data management within the West Jakarta Vocational High School is that there is no analysis and research on good and relevant information technology governance in every budget the boss funds issue. This study aims to determine the level of capability and gaps in information technology governance that is currently being implemented, namely the boss fund management information system (Rkas, Arkas, Ready Bop Bos and Headquarters). This study uses analysis based on the 2019 COBIT standard with a focus on the APO12 (Managed Risk) and APO13 (Managed Security) domains to produce a value of capability level that can be used as a reference for analyzing risk management and security management in boss fund management at all West Jakarta Vocational High Schools. The data used in this study came from interviews, questionnaires and direct observation to the research site. The audit results show. APO12 level 2 capability level with a value of 89.29% (Fully Achieved). The capability level of APO12 is level 3 with a value of 77.36% (Largely Achieved) where the capability level of Level 3 APO12 does not reach Fully Achieved so that the capability level of APO12 is at level 3 The capability level of APO13 level 2 with a value of 61.43% (largely Achieved) which does not reach Fully Achieved so The capability level of APO13 is at level 2. The results of this study provide recommendations for aligning the vision, mission, and objectives of boss fund management, so as to improve the function of the boss fund management information system in all SMKN West Jakarta.